2010
DOI: 10.1007/s00213-010-2049-7
|View full text |Cite
|
Sign up to set email alerts
|

Spatial memory alterations by activation of septal 5HT1A receptors: no implication of cholinergic septohippocampal neurons

Abstract: An action of 8-OH-DPAT on only MS cholinergic neurons is not sufficient to account for the drug-induced memory impairments. A concomitant 8-OH-DPAT-induced hyperpolarisation of cholinergic and/or GABAergic and/or glutamatergic neurons (intact rats), or of only GABAergic and/or glutamatergic ones after cholinergic lesion, might be necessary to obliterate task acquisition, confirming that, in the MS, (1) the three neuronal populations could cooperate to process hippocampal-dependent information, and (2) non-chol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…In addition, the strongest argument for a role of the HF in the control of spatial memory was provided by the discovery of ''place cells '' there (O'Keefe and Dostrovsky, 1971). Koenig et al (2011) postulated that, in the MS, the three neuronal populations (GABAergic, glutamatergic and cholinergic) could cooperate to process hippocampus-dependent information, and that noncholinergic septo-hippocampal neurons might be more important than are those that are cholinergic in serotonin-induced modulation of hippocampus-dependent memory processing. Kirby and Rawlins (2003) showed that there was no impairment in the spatial working memory of rats at seven days after lesion of the cholinergic neurons in the MS, although the rats were trained before the lesion.…”
Section: Neurochemical Aspectsmentioning
confidence: 99%
“…In addition, the strongest argument for a role of the HF in the control of spatial memory was provided by the discovery of ''place cells '' there (O'Keefe and Dostrovsky, 1971). Koenig et al (2011) postulated that, in the MS, the three neuronal populations (GABAergic, glutamatergic and cholinergic) could cooperate to process hippocampus-dependent information, and that noncholinergic septo-hippocampal neurons might be more important than are those that are cholinergic in serotonin-induced modulation of hippocampus-dependent memory processing. Kirby and Rawlins (2003) showed that there was no impairment in the spatial working memory of rats at seven days after lesion of the cholinergic neurons in the MS, although the rats were trained before the lesion.…”
Section: Neurochemical Aspectsmentioning
confidence: 99%
“…A combined sigma/5-HT 1A receptors agonist, OPC-14523, reverses scopolamine-and age-associated learning and memory deficits in passive avoidance or Morris water maze (MWM) (Tottori et al 2002). These effects might be mediated by an increase in ACh release in dorsal hippocampus (DH;Tottori et al 2002), although some studies demonstrated that noncholinergic neurons might play the main role in serotonin effects on hippocampal memory processing (Koenig et al 2011). Subcutaneous (s.c.) administration of 5-HT 1B receptor (5-HT 1B R) agonists impairs memory retention in onetrial PA.…”
Section: The Effects Of Serotonin On Cholinergic Transmissionmentioning
confidence: 99%
“…Multiple serotonin receptor subtypes have been found to be expressed in the BNST, to include 1A, 2A, 1B, 2C and 7 subtypes (Hazra, et al, 2012). Expression of serotonin receptors 1A (Koenig, et al, 2011), 2A (de Paula, et al, 2012 and type 3 (Urzedo-Rodrigues, et al, 2014) has been reported in the septum, while the subtypes 1A (Sun, et al, 2015) and 2C (Scopinho, et al, 2012) are expressed in the MeA.…”
Section: Septum Amygdala Bnst and Mesencephalonmentioning
confidence: 99%